Hillary Clinton’s Beliefs and Ideology Reflected Through Emotional Appeals in Political Discourse - Nguyen Thi Thanh Thanh, (Eximia, 2025)
This paper investigates how Hillary Clinton constructed and conveyed her political beliefs and ideological stance during the 2016 U.S. presidential campaign through emotional appeals in her speeches. Drawing on the principles of Critical Discourse Analysis (CDA) and Appraisal Theory, the study examines Clinton’s discursive strategies in relation to the socio-political context of the time, emphasizing how she employed intertextuality, emotional language, and ideological alignment to mobilize support, particularly among marginalized groups. The paper contrasts her rhetorical choices with those of Donald Trump to highlight the ideological polarization that characterized the 2016 election.